Iraqi Satellite Music Channels and Their Role in Spreading Negative Values among University Youth - Alsangri, Bushra Dawood Saba (ALBAHITH ALALAMI, 2013)
This study aims to clarify the role of Iraqi satellite channels in spreading negative values ​​among university youth; and the tendency of this segment to simulate the descending behaviors and pseudo-peculiar concepts of our society, which are displayed through the screens of these channels, based on the relevant media literature such as scientific references and the results of previous studies and research.The study followed the survey methodology to examine the public based on the questionnaire as a research tool, which was distributed to a sample of male and female students of Baghdad University enrolled in the university for the academic year 2011-2012.In order to achieve the specific objectives of this research, it has been divided into three topics: The first survey, the methodological framework of the research, which included the problem of research and research hypotheses and the importance of research and methodology and previous studies. The second investigation, dealt with the theoretical framework, which included Iraqi music channels and youth. Whereas, the third one, included the results of the field study, and interpretation of the tables attached as well as general findings and recommendations.The study reached a number of results, including:• More than half of the research sample is exposed to Iraqi satellite channels permanently, and most of the respondents watch satellite channels from two hours to less than 3 hours a day. The high rate of watch hours may leave the viewer behaved, especially young people to become a lot of scenes part of their personality and daily behavior.• Males and females agreed to simulate what is presented in these channels in terms of specialization, whether scientific or humanistic.• There are no significant differences in terms of gender, and the extent of the respondents' approval to impose censorship on the music channels.• The results of the field study indicate that the Iraqi satellite channels contribute to the dissemination of many negative behaviors and values, including the adoption of words and dancing movements, imitation of fashion, fluidity and spreading finery, etc. which achieved high rates and repetitions.Finally, the great spread of these channels and their impact on the mass culture cannot be ignored and must take this media phenomenon seriously, especially since the media studies that addressed this phenomenon are very few despite the space occupied by the broadcast, and with what offer of values many of them are not positive, and they contradict with the familiar values.